Analyzing The Intention of Borrower to Use Fintech Lending - Hasna; Yaser Taufiq Syamlan (Ekonomi Islam Indonesia, 2021)
This study aims to determine the direct effect of social influence, consumptive culture, and perceived usefulness on intention to use financial technology lending. This study also to find out the awareness people on using sharia fintech lending. Then, this study also to find out the indirect effect of social influence, consumptive culture, and perceived usefulness on intention to use financial technology lending moderated by motivation variable using Partial Least Square – Structural Equation Modeling (PLS-SEM) method. This research has found social influence and consumptive culture have a significant influence on intention to use fintech lending. Perceived usefulness and sharia fintech lending knowledge does not influence on intention to use fintech lending. This study found that social influence, consumptive culture, and perceived usefulness had no effect on the intention to use fintech lending through motivation as a moderating variable.